Energy efficiency and cell coverage area analysis for macrocell networks - Abdulkafi A.A.; Tiong S.K.; Koh J.; Chieng D.; Ting A. (2023)
The issues of energy efficiency and environmental protection are becoming critical issues for both fixed and wireless network operators worldwide. For wireless network operators, the challenge generally lies on providing maximum energy efficiency with largest possible coverage area. In this paper we first investigate the parameters affecting energy efficiency and the cell coverage area. We later analyze the relationship between area power consumption and transmission range (cell radius), transmission power, frequency band, shadowing and the path-loss exponent. From the analysis, optimal inter site distance that utilizing minimum area power consumption can be obtained for different percentage requirement of coverage area corresponding to minimum transmit power that achieves this degree of coverage. The optimal inter site distance is determined for macrocell without the impact of shadowing to be equal about 1250m with minimum area power consumption of 526 W/km 2. With the effect of shadowing, the optimal inter site distance and minimum area power consumption are 1050 m and 778.7 W/km 2 respectively. 2012 IEEE.